Advances in the cellular structural biology of nucleic acids - Giassa, Ilektra-Chara; Rynes, Jan; Fessl, Tomas; Foldynova-Trantirkova, Silvie; Trantirek, Lukas (FEBS letters, 2018)
Conventional biophysical and chemical biology approaches for delineating relationships between the structure and biological function of nucleic acids (NAs) abstract NAs from their native biological context. However, cumulative experimental observations have revealed that the structure, dynamics and interactions of NAs might be strongly influenced by a broad spectrum of specific and nonspecific physical-chemical environmental factors. This consideration has recently sparked interest in the development of novel tools for structural characterization of NAs in the native cellular context. Here, we review the individual methods currently being employed for structural characterization of NA structure in a native cellular environment with a focus on recent advances and developments in the emerging fields of in-cell NMR and electron paramagnetic resonance spectroscopy and in-cell single-molecule FRET of NAs.
Keywords: Animals; in-cell NMR; Cells; magnetická rezonanční spektroskopie; RNA; analýza jednotlivých buněk; buňky; Humans; Nucleic Acid Conformation; Nucleic Acids; DNA; nukleové kyseliny; Single-Cell Analysis; Models, Molecular; Electron Spin Resonance Spectroscopy; lidé; in-cell EPR; zvířata; elektronová paramagnetická rezonance; konformace nukleové kyseliny; molekulární modely; Magnetic Resonance Spectroscopy; in-cell single-molecule FRET; in-cell chemical probing